Corrosion durability of nanostructured TiAlYN coatings, deposited by PIII&D method from filtered vacuum-arc cathodic plasma - Vasyliev, V.V.; Luchaninov, A.A.; Sevidova, E.K.; Strel'nitskij, V.E. (Вопросы атомной науки и техники, 2015)
The electrochemical characteristics of nanostructured TiAlYN coatings deposited on 12X18H10T steel substrates are investigated in 3% aqueous solution of NaCl. The coatings were deposited from filtered vacuum-arc plasma by PIII&D method. Measurements of corrosion potentials Ecor and anodic polarization curves showed that the best protection against galvanic corrosion (GC) provides TiA1YN coating containing 0.2 at.% Y deposited on the substrate when applying pulsed bias potential of -1.5 kV amplitude. Addition DC bias potential of -150 V to pulse one leads to deterioration of the protective properties: activation potential of anodic processes (APAP) decreases in 3…4 times. Increase in TiA1YN coatings deposition rate promotes improvement their protective properties due to improved adhesion and decreased level of residual stress.